2021
DOI: 10.1094/phyto-08-20-0350-fi
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Post-Glacial Genetic Isolation and Human-Driven Migration in the Dothistroma Needle Blight Pathogen in Western Canada

Abstract: Many current tree improvement programs are incorporating assisted gene flow strategies to match reforestation efforts with future climates. This is the case for the lodgepole pine (Pinus contorta var. latifolia), the most extensively planted tree in western Canada. Knowledge of the structure and origin of pathogen populations associated with this tree would help improve the breeding effort. Recent outbreaks of the Dothistroma needle blight (DNB) pathogen Dothistroma septosporum on lodgepole pine in British Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Individual population studies have shown unexpected levels of diversity in many populations [20][21][22][23][24][25][26][27][28][29]. This diversity indicates that sexual reproduction is more common than previously thought, particularly as the sexual stage (previously known as Mycosphaerella pini) has only rarely been observed, and the asexual stage is ubiquitous.…”
Section: Introductionmentioning
confidence: 97%
“…Individual population studies have shown unexpected levels of diversity in many populations [20][21][22][23][24][25][26][27][28][29]. This diversity indicates that sexual reproduction is more common than previously thought, particularly as the sexual stage (previously known as Mycosphaerella pini) has only rarely been observed, and the asexual stage is ubiquitous.…”
Section: Introductionmentioning
confidence: 97%
“…However, many other biotic, abiotic and anthropogenic factors could be important drivers for needle blights epidemics. Among these, the movement of infected planting material between regions and countries is thought to be the main anthropogenic pathway of L. acicola, D. pini and D. septosporum [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study further confirm the suitability of this locus as a diagnostic for D. septosporum. The sample population of D. septosporum assembled for this study was geographically diverse, with samples representing the different geographic subgroups identified by Capron et al [4], as well as samples from Alaska, California, Oregon, and New Zealand, suggesting that the assay has wide applicability.…”
Section: Discussionmentioning
confidence: 89%
“…As historical distribution records in Canada are based on morphology, it will be necessary to use DNA-based methods to fully understand the geographic distribution of these pathogens. Development of a LAMP diagnostic assay for D. septosporum was prompted by the finding that this species was causing Dothistroma needle blight in Alberta [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation